H 2 S‐Responsive Carbon Dot‐Poly(α‐Lipoic Acid) Nanodrug Delivery Platform for Multimodal Antibacterial Therapy - Hongbo Juan; Xin Wang; Shan Sun; Kelly Kexin Lin; Jingxin Ma; Kefeng Zhou; Mingyan Zhao; Jianping Yang (Small, 2026)
ABSTRACT The overuse and misuse of antibiotics have accelerated the global antimicrobial resistance crisis, while the therapeutic efficacy of conventional antibiotics remains severely limited by dense biofilm barriers and the complex infectious microenvironment. To address these challenges, we developed an H 2 S‐responsive nanodrug delivery platform (PIP@CDs‐PαLA) based on multifunctional carbon dots (CDs) and poly(α‐lipoic acid) (PαLA), enabling efficient encapsulation of the broad‐spectrum antibiotic piperacillin (PIP) via a self‐assembly strategy. By integrating the intrinsic photothermal and photodynamic properties of CDs with antibiotic chemotherapy, the system achieves synergistic multimodal antibacterial therapy, enhancing bactericidal efficacy and reducing the risk of resistance. Light‐induced heat and reactive oxygen species (ROS) further disrupt biofilm architecture, facilitating antibiotic penetration. The platform exhibits precise responsiveness to elevated H 2 S levels in infectious microenvironments, enabling site‐specific drug release, while simultaneously depleting endogenous H 2 S to potentiate ROS‐mediated antibacterial activity. Both in vitro and in vivo evaluations demonstrate that the platform exhibits potent antibacterial activity and effective biofilm eradication, while also promoting infection resolution and tissue regeneration in a mouse abscess model. This study provides a robust strategy to overcome the limitations of conventional antibiotic therapies and offers a promising approach for intelligent antibacterial nanoplatforms.